Building an ontological modeling mechanism for virtual cities - Luis Casillas; Gilberto Vargas; Miguel Lares (ReCIBE, 2016)
Modeling of cities is certainly a challenge. Most of this complexity is caused by the significant number of variables, as well as the vast manifestation for their ranks. Diverse efforts have been conducted by different researchers, in order to achieve powerful representations. Some of these efforts are aimed at graphical representation, some others are aimed at functionality. Present effort is aimed at the scaffolding support for the representation and, eventually, functionality of virtual cities. Such infrastructure would support current and future efforts devoted to populating virtual cities with agents showing different behaviors and roles. These agents would be active and concrete elements in cities, such as pedestrians, cars or drivers, and some others would be dynamic synthetic-elements, such as traffic lights or drawbridges. These agents will populate the city model and manifest in future efforts from this research; current effort is mainly focused in the production of cities’ infrastructure. The generation and representation of a virtual city is, per se, a significant challenge. This paper focuses in such challenge.